Desain Robot Holonomic berbasis Roda Mecanum dengan Arm Manipulator - Budi Bayu Murti; Tirza Sarwono; Esa Apriaskar; Fahmizal Fahmizal (Universitas Syiah Kuala, 2020)
Movement systems of a mobile robot in an industry generally use the concept of differential drive or ackerman steering. However, both methods tend to have low mobility. This paper proposes an industrial mobile robot design with a holonomic concept using mecanum wheels to maneuver in all directions with better mobility. As a commonly used robot in the industrial field, an arm manipulator is combined with a mobile robot. The mobile robot and arm manipulator's mechanical design is made using software inventor and utilizing acrylic as its base material. The electronic design of the robot is created using Eagle software. After the robot manufacturing is complete, then a user interface is made using the processing IDE. Several robot tests are conducted to ensure that the designed robot runs appropriately. From the functional test results, parts of the robot can run well. The smallest error obtained is 5 cm for the robot heading test, and the most significant error is 20 cm. The testing of a servo motor, which is the arm manipulator's primary actuator, showed the highest error of only 2 degrees. Besides, the gripper of the arm manipulator can also hold objects properly.